The Influence of Job Promotion and Work Environment on Employee Performance Through Organizational Commitment at the Housing and Settlement Areas Service of Merangin Regency - Maruli Pane, Saut; Rozi Yamali, Fakhrul; Akbar, Ali (Journal of Accounting and Finance Management, 2025)
The role of Human Resources (HR) in an organization has an important position in the implementation of the organization's work process and the achievement of organizational goals. In its implementation, humans in this organization are the main element compared to other resources. Without human resources, other resources certainly cannot be utilized. This study aims to determine and describe the picture of job promotion, work environment, organizational commitment and performance of civil servants at the Housing and Settlement Service of Merangin Regency and to determine and analyze the influence of job promotion and work environment on the performance of civil servants through organizational commitment at the Housing and Settlement Service of Merangin Regency. The type of research uses descriptive verification research. This study uses the PLS analysis method. The results of the questionnaire on the description of the research variables that the total score of job promotion is 1989 in the good category. Then for the description of the work environment variable shows that the employee work environment is good with a score of 2648. Furthermore, the description of the organizational commitment variable shows that the organizational commitment score is 1981 in the high category. While the description of the employee performance variable shows that the score is 2649 with a high category Based on the results of the PLS analysis, job promotion and work environment have a positive and significant effect on organizational commitment. Then job promotion has a positive and significant effect on performance through organizational commitment at the Housing and Settlement Service of Merangin Regency. This means that the higher the job promotion, the organizational commitment and employee performance will increase. This study shows that job promotion and work environment have a significant effect on organizational commitment and employee performance. Therefore, academic suggestions for further researchers are to develop a research model by including other variables such as leadership, organizational culture, and job satisfaction in order to provide a more comprehensive understanding of the factors that influence employee performance.